2018
DOI: 10.1016/j.chemosphere.2018.05.092
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cd by ferrihydrite organo-mineral composites: Implications for Cd mobility and fate in natural and contaminated environments

Abstract: Adsorption and coprecipitation of organic matter with iron (hydr)oxides can alter iron (hydr)oxide surface properties and their reactivity towards nutrient elements and heavy metals. Organo-mineral composites were synthesized using humic acid (HA) and iron oxide, during coprecipitation with ferrihydrite (Fh) and adsorption to pre-formed Fh with two C loadings. The Fh-HA coprecipitated composites have a higher C content and smaller surface area compared to the equivalent adsorbed composites. NanoSIMS shows ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…In the case of Fe-coprecipitates, SROFe-OM are often described as spherical 2-5 nm ferrihydrite crystallites aggregated in an OM matrix (Chen et al, 2016;Eusterhues et al, 2008;Mikutta et al, 2008;Mikutta et al, 2014;Schwertmann et al, 2005). This model of Fe oxy-hydroxide occlusion in OM is well illustrated in several studies (Du et al, 2018;Eusterhues et al, 2014;Kleber et al, 2015). The density of SROFe-OM aggregates (Eusterhues et al, 2008;Guenet et al, 2017;Mikutta, 2011;Mikutta et al, 2008) together with the size of the ferrihydrite crystallites and their crystallinity (Eusterhues et al, 2008;Mikutta, 2011;Mikutta et al, 2010;Schwertmann et al, 2005) has been shown to vary with the experimental conditions.…”
Section: Introductionmentioning
confidence: 52%
“…In the case of Fe-coprecipitates, SROFe-OM are often described as spherical 2-5 nm ferrihydrite crystallites aggregated in an OM matrix (Chen et al, 2016;Eusterhues et al, 2008;Mikutta et al, 2008;Mikutta et al, 2014;Schwertmann et al, 2005). This model of Fe oxy-hydroxide occlusion in OM is well illustrated in several studies (Du et al, 2018;Eusterhues et al, 2014;Kleber et al, 2015). The density of SROFe-OM aggregates (Eusterhues et al, 2008;Guenet et al, 2017;Mikutta, 2011;Mikutta et al, 2008) together with the size of the ferrihydrite crystallites and their crystallinity (Eusterhues et al, 2008;Mikutta, 2011;Mikutta et al, 2010;Schwertmann et al, 2005) has been shown to vary with the experimental conditions.…”
Section: Introductionmentioning
confidence: 52%
“…For preparation of the Fh-HA binary composite, 0.1 M Fe 3+ salt solution was first reacted with two known amounts of HA solution for 2 h, generating C/Fe molar of 0.47 and 2.33, respectively, then subjected to a base hydrolysis to pH ~7.5. These preparations resulted in Fh-HA composites with approximately 5 wt% and 15 wt% C (Du et al, 2018b), and were abbreviated as FhHA_5%C and FhHA_15%C, respectively. Both pure Fh and Fh-HA composite were rinsed several times until no dissolved organic carbon (DOC) was detected in the supernatant liquid (Du et al, 2018b).…”
Section: Synthesis Of Ferrihydrite and Ferrihydrite-ha Binary Compositementioning
confidence: 99%
“…These preparations resulted in Fh-HA composites with approximately 5 wt% and 15 wt% C (Du et al, 2018b), and were abbreviated as FhHA_5%C and FhHA_15%C, respectively. Both pure Fh and Fh-HA composite were rinsed several times until no dissolved organic carbon (DOC) was detected in the supernatant liquid (Du et al, 2018b).…”
Section: Synthesis Of Ferrihydrite and Ferrihydrite-ha Binary Compositementioning
confidence: 99%
See 1 more Smart Citation
“…The model parameters derived from the single mineral system of ferrihydrite and δ‐MnO 2 can be applied to the mixed mineral systems. This is different from the mixed systems of minerals and organic matter, in which the interactions between minerals and organic matter may significantly affect the reactivity of the mixture (Christl and Kretzschmar, 2001; Du et al, 2018a, 2018b; Vermeer et al, 1999). However, if ferrihydrite and δ‐MnO 2 were precipitated together during synthesis, the As(V) adsorption and desorption behavior by the co‐precipitates may be different from that based on additivity of these two minerals, which desired further study.…”
Section: Resultsmentioning
confidence: 90%